Causal Factors Influencing Team Effectiveness in Schools under the Secondary Education Service Area Office Chonburi Rayong - Boonyalit, Natthaya; Phutiariyawat, Jantarat (Rajapark Journal, 2023)
The objectives of this research were: 1) to study the level of organizational context, team characteristic, team process and team effectiveness in schools. 2) to study the relationship of casual factors influencing team effectiveness in schools and 3) to find out the direct and indirect effects of the factors affecting the team effectiveness. The samples were 357 persons including teachers in schools under the secondary education service area office Chonburi Rayong, which were selected by stratified random sampling. The research instruments used were Likert scale questionnaires comprising 5 levels of data analysis. The statistics used for data analysis included percentage, mean, standard deviation, the Pearson product moment correlation coefficient and path analysis. LISREL was used for path analysis. The results of this research indicated that; 1) The levels of organizational context, team characteristic, team process and team effectiveness in schools were at a high level and each aspect was at a high level. 2) The relationship of inter correlations amongst causal factors and team effectiveness in schools were all significant. The casual factors correlated with team effectiveness. 3) The casual factors that had direct and indirect effects on team effectiveness in schools under the secondary education service area office Chonburi Rayong were as follow: (1) Direct effects occurred from two casual factors were team characteristic and team process. (2) Indirect effect from organizational context through team characteristic and team process toward team effectiveness in schools was significant.